ANALYSIS OF THE INFLUENCE OF DIFFERENT GNSS POSITIONING STRATEGIES ON RPA TRAJECTORY MODELING WITH PHOTOGRAMMETRIC APPLICATIONS - Busch, Patrick Otto; Lima Rodrigues, Tiago; Ercolin Filho, Leonardo (Ra’e Ga: o Espaço Geográfico em Análise, 2024)
The geodetic positioning of RPAs (Remotely Piloted Aircraft) via the Global Satellite Navigation System has gained relevance with the use of RTK (Real Time Kinematic) and PPK (Post-Processed Kinematic) positioning methods, which proposes a reduction in time and cost in photogrammetric support in the field. As long as the observables are recorded, the solution can be post-processed, independent of baseline extension (LB) and base correction signal reception via radio link. In this context, the company Guandalini Positioning has been developing a solution called GPPK (Guandalini PPK), which makes use of an on-board GNSS receiver (L1 or L1/L2 GPS, GLONASS) and a photo-sensor system to identify the exact moment of acquisition of the images. In this work, using GPPK, the influence of different GNSS PPK processing strategies was analyzed in the context of aero-photogrammetric surveys. Through statistical analysis, the trajectories obtained by each strategy could be considered statistically equal. Despite this, using the accuracy analysis of the results obtained based on checkpoints, it is clear that the use of a short LB presents better results than a long LB, possibly due to the occupation time and the restriction of the Emlid receivers (which makes up the GPPK) in working only with the L2C observable. Furthermore, the inclusion of the L2 carrier in short LB did not significantly influence the accuracy, as did the increase in the acquisition frequency of the observables.